Upregulation of Tolerogenic Pathways by the Hydrogen Sulfide Donor GYY4137 and Impaired Expression of H2S-Producing Enzymes in Multiple Sclerosis - Milica Lazarević; Giuseppe Battaglia; Bojan Jevtić; Neda Djedovic; Valeria Bruno; Eugenio Cavalli; Đorđe Miljković; Ferdinando Nicoletti; Miljana Momčilović; Paolo Fagone (MDPI AG, 2020)
The aim of this study was to examine the in vitro effects of the slow-releasing H2S donor GYY4137 on the immune cells involved in the pathogenesis of the central nervous system (CNS) autoimmune disease, multiple sclerosis (MS). GYY4137 specifically potentiated TGF-β expression and production in dendritic cells and significantly reduced IFN-γ and IL-17 production in the lymph node and spinal cord T cells obtained from mice immunized with CNS antigens. Both the proportion of FoxP3+ regulatory CD4+ T cells in the lymph node cells, and the percentage of IL-17+ CD4+ T cells in the spinal cord cells were reduced upon culturing with GYY4137. Interestingly, the peripheral blood mononuclear cells obtained from the MS patients had a lower expression of the H2S-producing enzyme, 3-mercaptopyruvate-sulfurtransferase (MPST), in comparison to those obtained from healthy donors. A significant inverse correlation between the expression of MPST and several pro-inflammatory factors was also observed. Further studies on the relevance of the observed results for the pathogenesis and therapy of MS are warranted.